Constructing an Andragogy Based Emotion Regulation Training Model to Develop the Self Efficacy of Nonformal Education Participants - Saepudin, Asep; Rindiani, Ani; Rosmia, Ade Romi; Boriboon, Gumpanat (Journal of Nonformal Education, 2026)
Background – Low self-efficacy among students is a barrier to completing their studies for students in non-formal education programs, who are generally adults. Therefore, andragogy-based emotional regulation is needed to develop student self-efficacy. Research Urgency – This article identifies self-efficacy issues among students in non-formal education programs in Bandung City, resulting from unstable emotional regulation. This leads to the development of a training model to improve student self-efficacy. Research Objective – This study aims to explore students’ self-efficacy and emotional regulation, and to develop a model to develop self-efficacy for students in non-formal education programs in Bandung City. Research Method – This study uses a qualitative approach to obtain in-depth and comprehensive information about the challenges faced by students in non-formal education programs. The chosen research method is Research and Development (R&D), which aims to identify problems and expectations while simultaneously developing a model to address these challenges. Research Findings – The main finding of this study is that students experience low self-efficacy due to unstable emotional regulation. Therefore, it is necessary to develop an andragogy-based emotional regulation training model to improve self-efficacy, consisting of input, process, and output aspects. Conclusion & Research Novelty – This study empirically identified the problem of low self-efficacy in students, which requires strengthening emotional regulation. Therefore, an andragogy-based emotional regulation training model was developed to develop student self-efficacy as a novelty in this research.